Changes in sensor recorded activity patterns and neuropsychiatric symptoms after deep brain stimulation for Parkinson’s disease: 5 case reports - Lena C. Bruhin; Michael Single; Aileen C. Naef; Katrin Petermann; Mario Sousa; Matilde Castelli; Ines Debove; Marie E. Maradan-Gachet; Andreia D. Magalhães; Andreas A. Diamantaras; M. Lenard Lachenmayer; Gerd Tinkhauser; et al. (BMC Neurology)
Abstract Background Effects of subthalamic nucleus deep brain stimulation (STN-DBS) on neuropsychiatric symptoms of Parkinson’s disease (PD) remain debated. Sensor technology might help to objectively assess behavioural changes after STN-DBS. Case presentation 5 PD patients were assessed 1 before and 5 months after STN-DBS with the Movement Disorders Society Unified Parkinson’s Disease Rating Scale part III in the medication ON (plus postoperatively stimulation ON) condition, the Montreal Cognitive Assessment, the Questionnaire for Impulsive-Compulsive Behaviors in Parkinson’s Disease Rating Scale present version, the Hospital Anxiety and Depression Scale and the Starkstein Apathy Scale. Steps taken per hour, nighttime spent in bed and time spent outside were monitored with a smartwatch and ambient sensors placed in patient homes for an average of 20 days pre- and postoperatively. Postoperative improvement in ICDs and concomitant anxious-depressive symptoms was observed in 3 patients and was accompanied by a decrease in steps taken per hour, as well as an increase in nighttime spent in bed. In the two patients without baseline ICDs, mild anxiety and apathy improved postoperatively, and no new neuropsychiatric symptoms occurred. Steps taken per hour did not decrease in these cases and nighttime spent in bed improved in one of the patients, but decreased in the other, who had experienced pain during OFF-phases at night before STN-DBS. Conclusion Changes in neuropsychiatric symptoms are associated with distinct activity patterns after STN-DBS, and wearable and ambient sensors may aid to capture those gradual shifts in behavior.